Manumissio inter amicos in the Light of Plautus’ Comedies - Tarwacka, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article concerns the informal method of slave manumission, which was the manumissio inter amicos. Plautus’ comedies seem to be a poorly used source of knowledge about this institution. It follows from them that the owner of the slave expressed in an imperative form the desire for manumission, while the amici, or witnesses, confirmed their presence and readiness to certify manumission, saying that they were happy about the freedom received by the slave.